Perancangan SOP Grading Kayu Log Jati sebagai Upaya Peningkatan Konsistensi dan Akurasi Proses Grading - Fitri Indah Puspitaningsih; Cheisa Raihan Atta Maulana; Fesa Putra Kristianto (Institut Teknologi Garut, 2026)
PT Philnesia International faced problems in the teak log grading process due to the absence of a standard operating procedure (SOP). Before the SOP was designed, grading was based on the experience of each grader, which often led to differences in perception regarding wood specifications. This situation resulted in errors in recording and price calculations, which impacted the company's profits. This study aims to develop a teak log grading SOP that can be used as a uniform reference for all graders, as well as to test its effectiveness in improving the consistency and accuracy of grading results at PT Philnesia International. The study uses a descriptive qualitative method with a data triangulation approach through interviews, observations, document analysis, and sampling tests. Spot checks were conducted on 100 samples before the implementation of the SOP and 100 samples after the implementation of the SOP. The results of the study showed a significant decrease in the number of errors, from 60 cases before the SOP to only 13 cases after the SOP was implemented. The implementation of the SOP has been proven to improve the consistency, efficiency, and accountability of the grading process. The existence of SOPs will help reduce errors in the grading process, which will have an impact on subsequent processes such as the final product price and buyer satisfaction with the quality of raw materials.